The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1415-47572014005000010
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papillomavirus (HPV) DNA and micronuclei in normal cervical cytology

Abstract: The aim of the present study was to investigate the association between HPV-DNA and micronucleus (MN) frequency in women with normal cervical cytology. A total of 158 normal cervical smears were analyzed cytologically. The HPV genome was amplified using the GP5+/bioGP6+ consensus primers. HPV-DNA of high-risk types 16, 18, 31, 33, 39, 45 and 59 were also investigated. Of the 158 samples, 20 (12.7%) and 47 (29.7%) were positive for HPV-DNA and MN, respectively. Evidence for MN was found in 11 out of 20 (55%) HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Although the mutagenic potential of both BPV [27,28,74,139] and HPV [29,30,140] is known, the molecular mechanisms that induce clastogenesis remains unknown. Mutagenic studies have attributed the BPV clastogenic potential to combined action of viral oncoproteins (E5, E6 and E7), that induce cell hyperproliferation and replication fork collapse [26,27,74,141].…”
Section: Oncogenic Virus and Ros Generation: A Field To Explorementioning
confidence: 99%
See 1 more Smart Citation
“…Although the mutagenic potential of both BPV [27,28,74,139] and HPV [29,30,140] is known, the molecular mechanisms that induce clastogenesis remains unknown. Mutagenic studies have attributed the BPV clastogenic potential to combined action of viral oncoproteins (E5, E6 and E7), that induce cell hyperproliferation and replication fork collapse [26,27,74,141].…”
Section: Oncogenic Virus and Ros Generation: A Field To Explorementioning
confidence: 99%
“…For this reason, mutagen identification has been explored [13][14][15][16], since to avoid the long term exposure to these mutagens can be considered a protective method against cancer. Currently, it is known that several drugs [16][17][18], organic [19][20][21][22] and inorganic chemical compounds [23,24] and biological agents, including viruses [12,[25][26][27][28][29][30][31][32][33] are able to induce DNA damage.…”
mentioning
confidence: 99%
“…Papillomaviruses (PVs) are a group of viruses with epithelium and mucous tropism [ 1 , 2 ]. PVs can infect all vertebrates, including rabbits [ 3 5 ], dogs [ 6 , 7 ], goats [ 8 ], humans [ 9 12 ], and bovines [ 1 , 13 15 ]. In the last decades, an increasing interest in studies involving these viruses has been observed [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exfoliated epithelial cells have been used in cytology to detect abnormal cells and to evaluate the diameters of nuclei and cytoplasm for cytomorphometric analysis and MN presence [8,9,10]. Samanta et al [11], Rosin and Anwar [8], Cortés-Gutiérrez et al [12] and Cassel et al [13] reported that infectious agents and cancer affect MN frequency in human cells. MN frequency was increased on cervicovaginal smears in human papillomavirus and Schistosoma haematobium infections, cervical intraepithelial lesions and carcinoma [8,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Samanta et al [11], Rosin and Anwar [8], Cortés-Gutiérrez et al [12] and Cassel et al [13] reported that infectious agents and cancer affect MN frequency in human cells. MN frequency was increased on cervicovaginal smears in human papillomavirus and Schistosoma haematobium infections, cervical intraepithelial lesions and carcinoma [8,11,12,13]. Although candidiasis is the most common fungal disease in the world, little information is known about the structural profile of epithelial cells in genital candidiasis.…”
Section: Introductionmentioning
confidence: 99%